Marijuana knowledge, confidence in knowledge, and information efficacy as the protective and risk factors of marijuana use among college students. Issue 2 (8th March 2022) - Park, Sung-Yeon; Ryu, So Young; Constantino, Nora; Yun, Gi Woong; Jennings, Enid; Fred, Daniel
Abstract: Objective This study explored the relationships between marijuana knowledge, confidence in knowledge, and information efficacy and marijuana use. Furthermore, the effects of the knowledge-related variables were examined on intention to use, resistance efficacy, and intention to vote for legalization. Participants: Undergraduate students ( N  = 215) were surveyed in Fall 2018. Methods: Data were collected online and analyzed through a series of regression analyses. Results: Higher knowledge was related to less use via higher perceived risk whereas higher confidence in knowledge was related to more use. Marijuana use was related to higher future intention to use, lower resistance self-efficacy, and intention to vote for legalization. Information efficacy was related to intention to vote for legalization only. Conclusions: Students with more knowledge were less likely to use marijuana, whereas students who considered themselves well-informed were more likely to use it. Future intervention efforts will benefit from counteracting students' misplaced confidence in their knowledge.